A Qualitative Analysis Into The Strategic Priorities of The Indonesian Bank Industry - Ridloah, Siti (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2016)
This research paper investigates present day strategic priorities employed by large (foreign exchange) banks in Indonesian banking industry. The research used âidea networkingâ of the mission statements of banks as the means to identifying a handful of priorities. The population comprised commercial banks in Indonesia. Foreign exchange banks in Indonesia were chosen as a sample of this study .The study was conducted in 2014. The research method utilized in this study is qualitative clustering through idea networking. In this method, the idea statements were extracted and linked to each other to produce diagrams resulting in clusters of statements that were generalized into priorities. The finding from this study is that Indonesian banks have six main priorities of âservice excellenceâ, âprudent corporate governanceâ, âinnovativeâ, âcustomer segmentation focusâ, âprofessionalismâ and âsocial responsibilityâ. This, undoubtedly, provides some insight into the potential threats to the Indonesian bank industry as well as an agenda for change.Penelitian ini mengkaji mengenai prioritas strategik pada bank-bank besar (valuta asing) dalam industri perbankan Indonesia. Penelitian ini menggunakan âidea networkingâ dari pernyataan misi bank sebagai sarana untuk mengidentifikasi beberapa prioritas. Populasi terdiri atas bank komersial di Indonesia. Bank valuta asing di Indonesia dipilih sebagai sampel penelitian ini. Penelitian ini dilakukan pada tahun 2014. Metode penelitian yang digunakan dalam penelitian ini adalah qualitative clustering melalui âide networkingâ. Dalam metode ini, pernyataan ide diekstraksi dan dihubungkan satu sama lain untuk menghasilkan diagram yang menghasilkan kelompok pernyataan yang digeneralisasikan ke dalam prioritas. Temuan dari studi ini adalah bahwa perbankan Indonesia memiliki enam prioritas utama âpelayanan primaâ, âtata kelola perusahaan yang bijaksanaâ, âinovatifâ, âfocus segmentasi pelangganâ, âprofesionalismeâ dan âtanggung jawab sosialâ. Hal ini, tidak diragukan lagi, memberikan beberapa wawasan ke dalam potensi tantangan terhadap industri perbankan Indonesia serta agenda perubahan.JEL Classification G3, G32